Интерференционные методы и приборы контроля качества - Гончар, В. В. (ХНУРЭ, 2012)
This work is devoted to one of the basic interferential control methods, namely the interferometric. There will also be reviewed quality control device, based on a Michel son interferometer.
Keywords: контроль качества; приборы контроля качества; интерференционные методы